The Effect of Workload and Work Discipline on Nurse Performance with Work Stress as an Intervening Variable - Nadella Kamalia Rifani; Masydzulhak Djamil Mz (Global Writing Academica Researching & Publishing, 2022)
In this study, job stress will be included as an intervening variable as we examine the impact of workload and work discipline on nurses' performance. The isolation room nurse at RSAU Dr. Esnawan Antariksa Halim Perdanakusuma in East Jakarta was the subject of this study. 35 nurses from the Dr. Esnawan Antariksa Halim Isolation Room at the RSAU in East Jakarta served as the study's sample. All people in the population are used as samples since the saturation sampling technique is used when there are fewer than 100 samples. The likert scale is used to measure the variables involved in this study. This study used questionnaires, a quantitative methodology, and structural equation modeling (SEM) with a partial least squares (PLS) technique for its analysis. SMARTPLS 3.0 software was utilized to process the data for this investigation. The results of this study indicate that employee performance can be maximized by optimizing work discipline and considering the workload that will be given to employees and work stress that will affect the improvement of the performance of nurses RSAU dr. Esnawan Antariksa Halim Perdanakusuma East Jakarta.